Leadership Communication Strategies in Enforcing Civil Servant Work Discipline in Takalar Regency Regional Government Agencies - Mujahid; Ahmad Leta; Andi Vita Sukmarini (Universitas Muhammadiyah Palu, 2026)
This study aims to describe leadership communication strategies in enforcing civil servant work discipline in Takalar Regency Regional Government. Furthermore, it aims to identify the obstacles or constraints faced by leaders in implementing communication strategies with employees. The research focuses on two regional government agencies with the lowest attendance rates: the Communication, Informatics, Statistics, and Cryptography Agency (Diskominfo-SP) with 79% and the Population Control, Family Planning, Women's Empowerment, and Child Protection Agency (Dinas PPKBPPPA) with 77%. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews with the Head of the Communication and Information Technology (Kominfo-SP) Office (Mr. Suhardianto, S.STP) and the Head of the PPKBPPPA Office (Mr. Drs. Sukwansyah), observations of fingerprint system usage, and analysis of ASN attendance documents and related regulations (PP No. 94 of 2021 and the Regent's Regulation on the TPP). The results indicate that leadership communication strategies are multi-channel, encompassing top-down vertical communication through morning roll calls and spot checks, digital communication through the fingerprint system, two-way communication through meetings and WhatsApp groups, and exemplary and persuasive communication through rewards and punishments. However, the implementation of these strategies remains inadequately adapted to the dominant nature of fieldwork in both Regional Apparatus Organizations. Interviews with both Agency Heads revealed a gap between formal disciplinary demands and the realities of mobile work, leading to resistance, demotivation, and internal conflict among OPD leaders. The study concluded that leadership communication strategies in Takalar Regency have increased ASN discipline awareness, but have not optimally accommodated the context of fieldwork. A more participatory and adaptive communication approach is needed to ensure effective and sustainable enforcement of ASN work discipline.